1991
DOI: 10.1128/jvi.65.9.4860-4866.1991
|View full text |Cite
|
Sign up to set email alerts
|

The full-length E6 protein of human papillomavirus type 16 has transforming and trans-activating activities and cooperates with E7 to immortalize keratinocytes in culture

Abstract: The wild-type E6 and E7 genes of human papillomavirus type 16 (HPV16) can cooperate to immortalize normal human keratinocytes in culture. The E6 open reading frame of HPV16 and other HPV types highly associated with cervical cancer has the potential of encoding both full-length E6 and two truncated E6* proteins, the latter being generated via splicing within the E6 open reading frame portion of the E6-E7 polycistronic transcript. Those types, such as HPV6, that are infrequently associated with cervical carcino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
1
3

Year Published

1993
1993
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(74 citation statements)
references
References 26 publications
4
66
1
3
Order By: Relevance
“…The potential to encode E6* proteins is an exclusive property of high-risk HPV types, but attempts to demonstrate that these oncoproteins possess transforming activity were unsuccessful (35). Pim and Banks have shown that HPV18 E6* protein was able to interact with both the full-length E6 and the E6-AP proteins in vitro and thereby to block the association of E6 with p53 (36).…”
Section: Discussionmentioning
confidence: 99%
“…The potential to encode E6* proteins is an exclusive property of high-risk HPV types, but attempts to demonstrate that these oncoproteins possess transforming activity were unsuccessful (35). Pim and Banks have shown that HPV18 E6* protein was able to interact with both the full-length E6 and the E6-AP proteins in vitro and thereby to block the association of E6 with p53 (36).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, for some pathogens, even an attenuated version may contain proteins whose function is deleterious, e.g. human papilloma virus (HPV) E6, which can cause transformation of infected cells, part of the pathophysiologic process whereby HPV causes cancer (15). A vector thus has the advantage of encoding only those proteins of the pathogen specifically desired for the immune response (and possibly proteins necessary for the vector, which can augment or detract from the desired immune response, as discussed below).…”
Section: Issues For Delivery Systems Based On Viral and Bacterial Vecmentioning
confidence: 99%
“…These high-risk mucosal HPV types also express a series of alternatively spliced transcripts in addition to the full-length E6 mRNA which encode truncated forms of E6 and are termed E6*. However, to date, attempts to demonstrate that these oncoproteins possess transforming activity were unsuccessful (9). For E6 and E7 oncoproteins, transforming activities are correlated, at least in part, with inactivation of p53 and pRb.…”
Section: Introductionmentioning
confidence: 99%